Ownership concentration and bank profitability - Peterson Kitakogelu Ozili; Olayinka Uadiale (Future Business Journal, 2017)
We investigate whether ownership concentration influences bank profitability in a developing country context. We focus on bank ownership concentration measured as the amount of direct equity held by a majority shareholder categorised into: high ownership concentration, moderate ownership concentration and disperse ownership. We find that banks with high ownership concentration have higher return on assets, higher net interest margin and higher recurring earning power while banks with dispersed ownership have lower return on assets but have higher return on equity. Also, higher cost efficiency improves the return on assets of widely-held banks and the return on equity of banks with moderate ownership. The findings have implications.
Keywords: G3; G31; G34; 650; Agency theory; Banks; Corporate governance; Firm performance; Ownership structure; Profitability; Return on asset; Return on equity